Informal task‐sharing practices in inpatient newborn settings in a low‐income setting-A task analysis approach - Gregory B. Omondi; Georgina A. V. Murphy; Debra Jackson; Sharon Brownie; Mike English; David Gathara (Wiley, 2020)
Abstract Aim To describe the complexity and criticality of neonatal nursing tasks and existing task‐sharing practices to identify tasks that might be safely shared in inpatient neonatal settings. Design We conducted a cross‐sectional study in a large geographically dispersed sample using the STROBE guidelines. Methods We used a task analysis approach to describe the complexity/criticality of neonatal nursing tasks and to explore the nature of task sharing using data from structured, self‐administered questionnaires. Data was collected between 26th April and 22nd August 2017. Results Thirty‐two facilities were surveyed between 26th April and 22nd August, 2017. Nearly half (42%, 6/14) of the "moderately critical" and "not critical" (41%, 5/11) tasks were ranked as consuming most of the nurses' time and reported as shared with mothers respectively. Most tasks were reported as shared in the public sector than in the private‐not‐for‐profit facilities. This may largely be a response to inadequate nurse staffing, as such, there may be space for considering the future role of health care assistants.